Bear Lake Athapaskan kinship and task group formation - Rushforth, Scott (Book collections on Project MUSE., 1984)
Revised version of doctoral thesis. Bear Lake people, Sahtugot'inc, are a group of northeastern Athapaskan Indians who reside in Fort Franklin, NWT. Contains a cultural description of kinship, friendship and the formation of task groups such as fishing, hunting and trapping parties.